As intrigas do Imperador : uma análise de narrativas biográficas sobre D. Pedro II - Alcântara, Mauro Henrique Miranda de (2019)
Emperor D. Pedro II is an emblematic character of our history. It reigned for almost half a century, between 1840 and 1889. The longevity of his reign alone is a matter of curiosity in a country that is marked, especially in the republican period, by institutional and governmental ruptures. Given this scenario, this character of Brazilian history has been revisited at various times since his deposition. Several biographical works have been published about him in the last century. From this perspective, we seek with this work to analyze how four of these biographical works, built intrigues to explain / represent it. We selected the works written by Benjamin Mossé-Baron of Rio Branco (1889), Gilberto Freyre (1925), Pedro Calmon (1975) and Heitor Lyra (1977) to analyze in the work. Our goal was to identify how biographers created and composed the character, in the relationship between documentation, character background and writing of the work. Thus, our hypothesis is that the biographer, in order to access the narrated character's past and explain it, mediates through narrative, using fiction as a binding-constructing element. To accomplish this task, we rely primarily on the concepts of French philosopher Paul Ricoeur, more specifically on the composition of intrigue and narrative temporality, and also on Raoul Girardet's writings on political mythology. With these tools, we seek to understand how biographers built a D. Pedro II martyr of national history.